If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(5z-1)(4-z)=0
We add all the numbers together, and all the variables
(5z-1)(-1z+4)=0
We multiply parentheses ..
(-5z^2+20z+z-4)=0
We get rid of parentheses
-5z^2+20z+z-4=0
We add all the numbers together, and all the variables
-5z^2+21z-4=0
a = -5; b = 21; c = -4;
Δ = b2-4ac
Δ = 212-4·(-5)·(-4)
Δ = 361
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$z_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$z_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{361}=19$$z_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(21)-19}{2*-5}=\frac{-40}{-10} =+4 $$z_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(21)+19}{2*-5}=\frac{-2}{-10} =1/5 $
| 4/9t=1/8 | | 445=15(s-50)+100 | | 3x-8=x+1× | | 3x-2/x-2=2/x+2 | | 3x+2+5x-11+x=180 | | x+3/2x-1=2 | | (5x+9)=(3x–5) | | 30=21-5(5-1w) | | (5x+9)°=(3x–5)° | | 7(3w+1)=-8 | | 1/5x–10=30 | | 30x-45=48x+11. | | 24=44-6(-4-1w) | | g^2–19g=0 | | g2–19g=0 | | a/8+6=1 | | 13.5/x=7.3 | | -2(3x)+6=4*(x-6) | | 7(p-89)=28 | | -2(3x)+6=4x(x-6) | | 2x/3=3x/4-7 | | X+(.06)x+(.05)x=21 | | 4-2b=-10 | | X+(.10)x=21 | | 9x-(5x+6)=6x-12 | | -4(3–p)=p–3 | | 5(u+81)=-20 | | 15x=-80 | | 35=-32-7x+11-6x | | 15=8x- | | 90=10(w-83) | | 3h-12=18 |